Extent of Participation of Respondents in Production and Broadcasting Programme of Community Radio - Krishna D.K., N.V. Kumbhare, R.N. Padaria, Premlata Singh; Arpan Bhowmik (Indian Journal of Extension Education, 2018)
The community radio has made an impression in all grounds of rural society in which there was a need to assess socio-technological empowerment of rural households. The study was taken up to compare the status of community members’ participation in community radios, operational under three different hosting agencies i.e. State Agricultural University (SAU), Krishi Vigyan Kendra (KVK) and Non-Government Organization (NGO). The community radio stations namely Pantnagar Janvani (G.B. Pant University of Agriculture and Technology), Pravara (KVK, Ahmednagar) and Yeralavani (Yerala Projects Society, Sangli) were selected purposively. Four villages have been selected randomly from one purposively selected block. Forty (40) respondents from four randomly selected villages from each CRS coverage area/ broadcast range along with 10 staff members of each CRS were selected for the study. Thus, a total of 150 respondents constituted the sample for the study. About 43 per cent of respondents had low level of participation in programme production and broadcasting followed by moderate level (40 %) and high level (17.50 %). Education and perception about CRS programmes were significantly influencing extent of participation of respondents.